ANALYSIS OF THE K-NEAREST NIGBOAR METHOD TO DETERMINE THE ELIGIBILITY OF INTERNSHIP STUDENTS AT PRIMA INDONESIA UNIVERSITY - Shriram ram; Medalsan C; Yanmil V. H. Purba; Jepri Banjarnahor (INFOKUM, 2022)
This study discusses how to determine the feasibility of interns who deserve to be awarded, by applying the K-NN method. Based on the problem in this study, it is difficult to determine prospective interns who will be rewarded for those who have special abilities, so this system aims to solve these problems using the K-NN method.. In this study, we have tested data with 5 types of criteria, where in this test we will try to collect the values that will be processed individually by inputting the values 1, 3, 4 and 2. Based on calculations, with discipline: 1, Have Expertise: 2, Able to Work in Team: 3, Able to communicate well: 1, then the result: Decent.